PROFITABILITY PROFITABILITY, FIRM SIZE, CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, AND FIRM VALUE: INTRODUCTION - La Ode Anto, La Ode Anto (Archives of Business Research, 2021)
This study aims to determine the effect of profitability and firm size on firm value through the disclosure of Corporate Social Responsibility (CSR Disclosure). The sample in this study was 105 objects of observation obtained using purposive sampling technique from manufacturing companies listed on the Indonesia Stock Exchange. The analytical method used is descriptive analysis and path analysis. The results show that profitability has a negative and significant effect on CSR disclosure but is positive and significant on firm value, while firm size has a positive and significant effect on CSR disclosure but is positive and not significant on firm value, while CSR disclosure has a positive and significant effect on firm value and able to mediate the effect of profitability and firm size on firm value.